AKT and heart remodelling: too much of a good thing?: Editorial - Wardman, Rhys; Heineke, Jörg (European heart journal, 2025)
This editorial refers to ‘Checkpoint kinase Wee1 activation drives inflammation and hypertrophy through the protein kinase B/phosphoinositide 3-kinases-nuclear factor κB pathway in cardiomyocytes’, by M. Wang et al., https://doi.org/10.1093/eurheartj/ehaf349.It has long been established that the serine/threonine kinase AKT plays a central role in physiological and pathophysiological signalling responses in the heart. As a key downstream node of phosphoinositide 3-kinase (PI3K), AKT relays extracellular signalling cues in order to coordinate metabolic and structural rearrangements widely thought to have beneficial effects on the heart.1 Indeed, AKT has been classically seen as a cardio-protective molecule by promoting cardiomyocyte survival and function, regulating key processes such as hypertrophy, angiogenesis, and stress adaptation in order to promote physiological growth whilst preventing pathological hypertrophy and cardiac dysfunction.1,2 For example, previous work has shown that transient activation of AKT enhances myocardial contractility and may delay the progression of heart failure, as well as inhibiting cardiomyocyte death by inhibiting proapoptotic factors such as BAD and caspase-9, preserving cardiomyocyte function following transient ischaemia. Moreover, AKT-driven substrate phosphorylation in cardiomyocytes promotes angiogenesis by increasing vascular endothelial growth factor A (VEGF-A) and Angiopoietin 2 levels to maintain myocardial vascular density.3-6